Managing the reliability of structures in the mechanism of implementation of end-to-end technologies in innovative ecosystem of the department - V. V. Galayko; A. A. Karpekin (Вестник Северо-Кавказского федерального университета)
Introduction. An innovative ecosystem is a condition for achieving the effectiveness of innovations in the mechanism for implementing end-to-end technologies, through managing the reliability of structures carried out at regional enterprises. It has a particular impact on the development of regional industry, ensuring a reduction in the cost of products and economic sectors through the production of high-tech products.Goal. The study identifies the problems affecting the reliability of structures in the system of implementation of end-to-end technologies and specifies the prospects for stimulating scientific research and practical application of new materials that improve the quality of training of specialists.Materials and methods. The research is based on analysis and analytical search work in the scientific sources, patent information databases and online data. Research methods are general scientific analysis, synthesis, generalization, modeling, etc., as well as specialized scientific methods in the form of generating innovations, using material for a new purpose, graphical and comparative analysis.Results and discussion. The influence of the department’s ecosystem on the formation of a culture of implementing end-to-end technologies in mechanical engineering in the educational process, increasing the level of professional training of innovator specialists and creating conditions for their successful career in the future was specified. The technology for manufacturing a shaft from an innovative composite basalt hybrid material is proposed, which is a more advantageous solution for end-to-end technologies, combining high strength, durability and lightness of the material used.Conclusion. Based on the results of the study, the authors conclude that the innovative competencies of students to generate innovations in the ecosystem of the department are represented as a tool for implementing end-to-end technologies in mechanical engineering.